Research on Physical Training Methods Related To the Use of Weapons by the Police - Hua-Sun, Zhao (Asian Journal of Social Sciences and Management Studies, 2016)
The use of weapons is the most advanced form of force for police to stop the crime, but also an important embodiment of the authority of the police law enforcement. Over the years, the using of firearms for police in the physical training has been based on the training method of the shooting sports team, it is just focus on firing accuracy and ignoring the police professional characteristics, which cause certain effect to police in the critical moment when police use weapons. This article starting from the characteristics of the police profession, according to the working characteristics of the current status of China’s police, put forward physical training methods relate with the police use weapons. It is a reference for the establishment of the physical training system for the use of weapon based on the characteristics of police professional and helping the majority of police improving the weapons use ability.